Two pathogen loci determine Blumeria graminis f. sp. tritici virulence to wheat resistance gene Pm1a. Issue 4 (18th March 2023) - Kloppe, Tim; Whetten, Rebecca B.; Kim, Saet‐Byul; Powell, Oliver R.; Lück, Stefanie; Douchkov, Dimitar; Whetten, Ross W.; Hulse‐Kemp, Amanda M.; Balint‐Kurti, Peter; Cowger, Christina
Summary: Blumeria graminis f. sp. tritici ( Bgt ) is a globally important fungal pathogen of wheat that can rapidly evolve to defeat wheat powdery mildew ( Pm ) resistance genes. Despite periodic regional deployment of the Pm1a resistance gene in US wheat production, Bgt strains that overcome Pm1a have been notably nonpersistent in the United States, while on other continents, they are more widely established. A genome‐wide association study (GWAS) was conducted to map sequence variants associated with Pm1a virulence in 216 Bgt isolates from six countries, including the United States. A virulence variant apparently unique to Bgt isolates from the United States was detected in the previously mapped gene AvrPm1a ( BgtE‐5612 ) on Bgt chromosome 6; an in vitro growth assay suggested no fitness reduction associated with this variant. A gene on Bgt chromosome 8, Bgt‐51526, was shown to function as a second determinant of Pm1a virulence, and despite < 30% amino acid identity, BGT‐51526 and BGTE‐5612 were predicted to share > 85% of their secondary structure. A co‐expression study in Nicotiana benthamiana showed that BGTE‐5612 and BGT‐51526 each produce a PM1A‐dependent hypersensitive response. More than one member of a B. graminis effector family can be recognized by a single wheat immune receptor, and a two‐gene model is necessary to explain virulence to Pm1a .